Trace Crawler - Umamahewari, E.; S, Krishnaveni; Gao, Xiao-Zhi (International Journal of Engineering and Technology, 2018)
The Object Request Broker (ORB) manages the interaction between clients and servers using the Internet InterORB Protocol (IIOP). The ORB trace file comprises of messages, trace points, and wire tracing. These trace files are usually large and at times they can grow to 1-2 GBs. For debugging an ORB problem, the developer must determine whether the problem is in the client or in the server of the distributed application. Typically during debugging process, developer have to switch between source codes and trace logs back and forth multiple times. Often browsing the right source code file, opening it in the IDE and then moving to the line from where the trace is originated. This work proposes a tool which will help developers and service engineers to browse through source code and corresponding trace by providing integrated framework. The Aim of the tool is to build an application to parse and analyse ORB trace files. The application will fetch relevant details for the failing entries, and will perform the preliminary analysis. In this way a lot of time and human effort can be saved. The customers such as defense, military organizations can themselves view relevant details about the failures of their application by this tool, without having to compromise on confidentiality with minimal effort and time.Â Â